Sea level rise effects on acidic pollution in a coastal acid sulphate soil area - Phong, N.D.; Hoanh, Chu Thai; To Phuc Tuong; Wassmann, Reiner (2014)
Bac Lieu is a coastal province the Mekong River Delta (MRD), Vietnam. Aside from salinity intrusion from the sea, the province is strongly affected by acidic pollution as 58% of the area (250,000 ha) is overlaid with acid sulphate soil (ASS). Previous studies showed that the eminent sea level rise (SLR) would influence the hydrology and salinity of the canal networks in the province. This study, using the previously validated hydraulic and water quality model VRSAP-ACIDITY (Vietnam River Systems And Plains, coupled with ACIDITY Module), aimed at quantifying impacts of different SLR scenarios (SLR = 17, 30, 50, or 75 cm) on acidic pollution in the province. Under the present sea level, widespread acidic pollution (pH < 5) of surface water occurred at the start of the rainy season, due to leaching of acidity from canal embankments and fields in ASS. The acceleration of SLR reduced the area of acidic polluted water. The lessening in acidic pollution was attributed to (1) SLR that raised the water level in the Mekong River, increasing the amount of fresh water flowing into the study area; and (2) the amount of water drained out of the study area increased, bringing with its acidity. It concluded that SLR has a positive effect on acidic pollution in the ASS coastal area.